The Combined Influences of Exercise, Diet and Sleep on Neuroplasticity - Pickersgill, Jacob W.; Turco, Claudia V.; Ramdeo, Karishma; Rehsi, Ravjot S.; Foglia, Stevie D.; Nelson, Aimee J. (Frontiers in Psychology, 2022)
Neuroplasticity refers to the brain’s ability to undergo structural and functional adaptations in response to experience, and this process is associated with learning, memory and improvements in cognitive function. The brain’s propensity for neuroplasticity is influenced by lifestyle factors including exercise, diet and sleep. This review gathers evidence from molecular, systems and behavioral neuroscience in human and animal models to explain how these three key lifestyle factors influence neuroplasticity alone and in combination with one another. This information will have implications for research, educational, fitness and neurorehabilitation settings.